Therapeutic Molecules for Fumigating Inflammatory Tumor Environment - Harikrishnan, Adhikesavan; Veena, Vijaykumar (Current Signal Transduction Therapy, 2018)
Background: Cancer is a complicated genetic disorder which is a major global health issue. The complexities of several cancer therapies are due to heterogenic nature of tumor and its microenvironment that is highly inflammatory and acidic. Thus, cancer related inflammation (CRI) is responsible for metastasis, resistance and recurrence of cancer. Although, several researches are being investigated, still emphasis is being made extensively on targeting the acidic and heterogenic inflammatory conditions in the tumor microenvironment. The present review article has focused on the different aspects of cancer to advanced strategies in cancer therapy. Objective: The review majorly focused on several molecules that are reported for preliminary, preclinical and clinical trials. Some important aspects are discussed in detail. Method: Several research findings were carefully reviewed and the conclusion made is based on the strong evidences that have been reported. Exclusively, the molecules targeting cellular signalling pathways of the different compartments of tumor microenvironment and inflammatory state are also reported. Results: Based on the strong evidences, we were able to document few molecules of natural and synthetic origin for cancer therapy targeting an important aspect of cancer. In this review, we have focused on the molecules that target the important cellular signalling pathways especially with respect to photodynamic and multi-targeted therapies that are in preliminary, preclinical and clinical trials. Conclusion: Although, the advanced cancer therapeutics have been established but the combination of different strategies is very important. The efficiency of the treatments depends on the stage of cancer and response of patients. Search for closely defined and selective molecular targets for a particular therapy is very complicated due to heterogenic nature of tumor environment, different therapeutic agents, incubation time, exposure doses and selectivity of therapy. The most promising photodynamic therapy (PDT) and multi- targeted therapies are being established but the question whether the cellular proteins that are most susceptible to the therapies has to be addressed. An important aspect that needs to be addressed is whether cancer is vulnerable to the particular therapy that selectively induces cell death in the cancerous tissue and inflammatory cells in tumor microenvironment that is a very challenging aspect of research in cancer treatment strategies. Hence, in this review, we focused on different therapeutic strategies for targeting multi- components of the fumigating inflammatory tumor environment.
Keywords: Globoscan